The Role of the Alliance for Women and Children (APPA) Bojonegoro in Dealing with Toxic Family Relationships from the Perspective of Mubadalah - Dyana, Burhanatut; Listyorini, Indah; Rofi'i, Hilmi Yusron (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Family problems are a common phenomenon in society. The number of marriages that are not harmonious, and the inequality in the relationship between husband and wife, ultimately leads to toxic relationships in the family. Examples of toxic relationships that often occur are infidelity, domestic violence, social inequality and others that cause discomfort in household relationships. This study aims to look at the role of the Bojonegoro Alliance for Women and Children (APPA) community in responding to the phenomenon of toxic relationships such as domestic violence, not being provided for, infidelity and others that often occur in families and how to prevent and then overcome such cases. The method used is descriptive analysis with a field research model using interviews and data research at the Bojonegoro Alliance for Women and Children (APPA), which has handled many such cases. The first stage is to analyse the field and cases of toxic relationships in the community, then conduct in-depth research and interviews with the object of study and then analyse the data linked to the concept of Mubadala in the family. The result of this research is that women's organisations are very helpful in preventing toxic relationships in the family. As well as helping women deal with the problem of violence in the family in the form of legal and psychological assistance after the incident.